NHERI Centrifuge Facility: Large-Scale Centrifuge Modeling in Geotechnical Research - Boulanger, Ross W.; Wilson, Daniel W.; Kutter, Bruce L.; DeJong, Jason T.; Bronner, Colleen E. (Frontiers in Built Environment, 2020)
The 9-m and 1-m radius geotechnical centrifuges at the Natural Hazards Engineering Research Infrastructure (NHERI) facility at the University of California at Davis provide the national research community with open access to unique and versatile modeling capabilities for advancing methods to predict and improve the performance of soil and soil-structure systems affected by earthquake, wave, wind, and storm surge loadings. Large-scale centrifuge models are particularly effective for the building of basic science knowledge, the validation of advanced computational models from the component to the holistic system level, and the validation of innovative soil remediation strategies. The capabilities and unique role of large-scale centrifuge modeling are illustrated using three example research projects from the shared-use NHERI facility. Education impacts stemming from operations activities and coordination of activities by the center's user base are discussed. Future directions and opportunities for research using the NHERI facilities are discussed.